Women’s Islamic education in Kartini’s and Rahma El Yunusiah’s thought: A comparative analysis - Nurul Hidayatillah; Lukman Hakim (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2023)
Although Islam accords women a dignified position, unequal access to education, gender discrimination, and limited opportunities for women’s empowerment remain persistent challenges, highlighting the need to strengthen the paradigm of Islamic education. This study comparatively examines the educational thought of Raden Ajeng Kartini and Rahma El Yunusiah on Islamic education for women to formulate a model for developing Islamic education in Indonesia. This study employed a qualitative, descriptive-analytical design based on library research. Data were collected from primary and secondary documents through documentary analysis and examined using content analysis, reflexive thematic analysis, and qualitative comparative analysis. Trustworthiness was ensured through source triangulation, peer debriefing, and repeated document review. The findings indicate that both Kartini and Rahma El Yunusiah regarded education as the primary instrument for women’s empowerment, but adopted different strategies. Kartini emphasized the transformation of consciousness through social critique, moral education, and spirituality, whereas Rahma El Yunusiah implemented this vision through Islamic educational institutions focused on strengthening religious faith, moral character, leadership, and the development of female educators. Despite these differences, both pursued the common objective of enhancing women’s dignity, capacities, and social participation. The study concludes that their educational thought represents two complementary empowerment strategies, conceptual and institutional transformation, that together form an inclusive, character-based, and gender-equitable paradigm of Islamic education. It contributes to the literature by proposing an integrative model of women’s empowerment and by providing a conceptual framework for developing policies, curricula, and educational practices that promote inclusivity, character formation, and gender justice.